Rice Husk Ash as an Admixture of M30 grade Concrete Exposed to Sulfate Environment - V.Rambabu, P; V.RamaRao, G (International Journal of Engineering and Technology, 2018)
In the present critique, Rice Husk Ash (RHA) partly replaced with cement in the quotient of 0%, 5%, 10%, 15%, and 20% to fruitage M30 grade Concrete. Concrete cubes divulged to Magnesium Sulfate and Sodium sulfate concentrations of 1%, 3% and 5% for the perpetuation of 28, 60and 90 days.   The Experimental data demonstrate that RHA improved the counteraction to sulfate attack on concrete and can be used as an Admixture, 10% as most favorable replacement quotient of RHA in cement.